Eating disorders in sports and football: An updated review - Diaz Ceballos, Isabel; Godoy-Izquierdo, Débora; Navarrón Vallejo, Estefania; Ramirez Molina, María José; Dosil Díaz, Joaquín (Cuadernos de Psicología del Deporte, 2018)
Disordered eating behaviours and eating disorders (EDs) are prevalent among athletes both at clinical and subclinical levels. This review briefly summarizes and updates the main findings on EDs in sports, with a specific focus on football, a largely ignored athletic modality in which EDs are common and more frequent than expected. We begin presenting EDs in sports and their prevalence. We review the traditional classifications of sports as "low-" and "high-risk" athletic modalities based on prevalence rates and examine recent findings that question the utility of classifying sports and estimating an athlete’s vulnerability for developing an ED based only on such dimension. We then focus on other more decisive risk factors involved in the predisposition, precipitation and maintenance of an ED in sports, including socio-cultural, psychosocial, behavioural and athletic-contextual factors. We reflect on current trends in sports and football that may contribute to an increased risk for EDs. Next, recommendations for preventing and managing EDs in sports are discussed, stressing the importance of reducing putative risk factors. Finally, we attend to future areas of research that may enrich our knowledge on this topic, including methodological, empirical and conceptual issues that may lead to further advancements in research and intervention.